Toxoplasma gondii HSP90: potential roles in essential cellular processes of the parasite - Ángel, Sergio Oscar (2014)
Hsp90 is a widely distributed and highly conserved molecular chaperone that is ubiquitously expressed throughout nature, being one of the most abundant proteins within non-stressed cells. This chaperone is up-regulated following stressful events and has been involved in many cellular processes. In Toxoplasma gondii, Hsp90 could be linked with many essential processes of the parasite such as host cell invasion, replication and tachyzoite-bradyzoite interconversion. A Protein-Protein Interaction (PPI) network approach of TgHsp90 has allowed inferring how these processes may be altered. In addition, data mining of T. gondii phosphoproteome and acetylome has allowed the generation of the phosphorylation and acetylation map of TgHsp90. This review focuses on the potential roles of TgHsp90 in parasite biology and the analysis of experimental data in comparison with its counterparts in yeast and humans.